Adductor Pollicis Muscle Thickness and Obesity Are Associated with Poor Outcome after Stroke: A Cohort Study - Souza, Juli Thomaz de [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo Antônio Mamede [UNESP]; Polegato, Bertha Furlan [UNESP]; Ribeiro, Priscila Watson [UNESP]; Bazan, Silméia Garcia Zanati [UNESP]; Braga, Gabriel Pereira [UNESP]; Luvizutto, Gustavo José [UNESP]; de Paiva, Sérgio Alberto Rupp [UNESP]; Bazan, Rodrigo [UNESP]; Azevedo, Paula Schmidt [UNESP] (Elsevier, 2018)
Background: Nutritional status may influence outcome after stroke. It is possible that some obese individuals present reduced fat-free mass. Aims: We aimed to determine if bedside evaluation of body composition by the body mass index (BMI), adductor pollicis muscle thickness (APMT) and arm muscle area (AMA), and the combination of low APMT or AMA with obesity are associated with disability 90 days after stroke. Methods: A cohort study evaluating 120 patients hospitalized at the Stroke Unit was carried out. Data were expressed as average ± standard deviation or median and percentiles. Obesity was evaluated by BMI and fat-free mass by the APMT and AMA. Receiver operating characteristic (ROC) curves and multivariate logistic regression analysis were used to measure whether APMT and obesity were associated with modified Rankin Scale (mRS) ≥3 (disability) within 90 days of stroke. The data were adjusted for National Institutes of Health Stroke Scale (NIHSS), sex, age, type of stroke, and thrombolysis. The significance level was 5%. Results: Of 120 patients, we came up with the following demographics: men: 66 (55.0%); mean age: 66.6 ± 13.2 years; ischemic stroke: 109 (90.8%); mean NIHSS: 4 (2-10); thrombolysis: 18 (16.5%). Considering mRS ≥3, ROC curve analysis showed that the value of the cutoff for APMT was <12.5 mm. In multivariate analysis adjusted for the above factors, each 1 mm of increase in APTM reduced the chance of disability by 31%. The intersection of obesity with APMT <12.5 mm increased by 37-fold the risk of disability. AMA was not associated with mRS ≥3. Conclusion: Lower APMT alone or in combination with obesity was associated with poor functional status.
Keywords: disability evaluation; nutritional assessment; obesity; Stroke